KINETICS OF THE ACCUMULATION RADICAL WITH PROVISION FOR REACTIONS 1-st AND 2-nd ORDER AT IRRADIATION ELECTRON INPULSED MODE - Aliev, B. A.; Potanin, A. S.; Partizan, G. (Recent Contributions to Physics, 2009)
In work is considered process radiation accumulations radical, their annihilations and first order interaction. Deduct defining recurrence correlation. The Got constants show get prettier correlation of the result with experimental dependency data of internal friction from time in process and after irradiation of the polymer electron.